Approaches of the competitiveness at the macroeconomic level - MIREA, Viorica; MIREA, Gabriel (Annals of Spiru Haret University. Economic Series, 2011)
In this article we approach gradually the competitiveness. Thus we present in the introduction some definitions of this concept, although there isn’t a widely accepted definition for this term. Then, we present how this indicator can be measured and used to achieve the national or European strategies. Taking into account the current economic and financial crisis, we presented the measures approved by the Romanian Government for this stage and their effects on the productivity and competitiveness.